Double-sided adhesive sheet, laminate and display device
The double-sided adhesive sheet, formulated with specific (meth)acrylic copolymer and monomers, addresses the issue of copper mesh visualization by achieving high oxygen permeability and excellent adhesion, thereby improving the visibility and design of display devices.
Patent Information
- Application Number
- JP2023084166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-05-22
AI Technical Summary
Conventional adhesive sheets fail to suppress visualization of copper meshes when laminated to transparent conductive copper films, especially under high temperature environments.
A double-sided adhesive sheet is developed using a pressure-sensitive adhesive composition containing (meth)acrylic copolymer, specific monomers, and an organotin compound, which is photocured to achieve high oxygen permeability and suppress visualization of the copper mesh.
The adhesive sheet effectively suppresses visualization of the copper mesh even when laminated to transparent conductive copper films, enhancing the visibility and design of display devices.
Smart Images

Figure 0007663104000003 
Figure 0007663104000001 
Figure 0007663104000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a double-sided pressure-sensitive adhesive sheet, a laminate, and a display device. [Background technology]
[0002] In recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels have been widely used in various fields. Touch panels are of various types, including resistive and capacitive types, with the capacitive type being the most commonly used. In the manufacture of display devices equipped with these touch panels, transparent adhesive sheets are used to bond optical components, for example, to bond a display device and an input device.
[0003] Traditionally, metal oxides such as ITO (indium tin oxide) have been widely used for the transparent conductive film of touch panels. ITO is a transparent and conductive material, but its conductivity is known to be inferior to that of metals such as copper. For example, using ITO for the transparent conductive film of large-screen touch panel sensors has been problematic, as it can sometimes make it difficult to maintain detection accuracy. For this reason, the use of a metal mesh such as copper for the transparent conductive film of touch panels is being considered.
[0004] However, because metal meshes such as copper have a metallic luster, they reflect external light, making the copper mesh (copper wiring) visible, reducing the transparency of the transparent conductive film and the visibility and design of the touch panel. For this reason, studies have been conducted to suppress reflection by overlaying a black oxide film on the copper mesh. For example, Patent Document 1 discloses a conductive laminate for a touch panel, which includes a light-transmitting substrate, a light-transmitting underlayer, a first copper oxynitride layer located on the underlayer's surface opposite to the surface that contacts the substrate, a copper layer located on the first copper oxynitride layer's surface opposite to the surface that contacts the underlayer, and a second copper oxynitride layer located on the copper layer's surface opposite to the surface that contacts the first copper oxynitride layer. Patent document 2 also discloses a method for manufacturing a touch panel sensor, which includes the steps of: preparing a double-sided film material by bonding a first single-sided film material having a metal layer and a blackened metal layer in that order on one main surface of the film substrate and a second single-sided film material having a blackened metal layer and a metal layer in that order on one main surface of the film substrate together using an adhesive or bonding agent; simultaneously etching the metal layers of the double-sided film material using a photolithography method with double-sided exposure to form a metal wiring pattern; and bonding a cover glass to the blackened metal layer side using an adhesive or bonding agent and then bonding the film substrate to the metal layer side. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 136117 [Patent Document 2] Japanese Patent Application Laid-Open No. 2015-125563 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the inventors' investigations revealed that when a conventional adhesive sheet is attached to a transparent conductive film having a copper mesh overlaid with a blackened film and the film is placed in a high-temperature environment, for example, the hue of the blackened film changes and the copper mesh becomes visible.
[0007] Therefore, in order to solve these problems of the conventional technology, the inventors conducted research with the aim of providing an adhesive sheet that can suppress the visualization of copper mesh even when the adhesive sheet is attached to a copper mesh-based transparent conductive film. [Means for solving the problem]
[0008] Examples of specific embodiments of the present invention are given below. [1] A (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms; a bifunctional (meth)acrylic acid ester monomer (B2) in which a reactive functional group is linked by a linking group derived from a linear diol having 4 to 12 carbon atoms; a photopolymerization initiator (C) other than a hydrogen abstraction type polymerization initiator; A double-sided PSA sheet obtained by photocuring a PSA composition containing an organotin compound (D), The oxygen permeability (P) of the double-sided PSA sheet was measured and calculated using the following method. A ) is 2000ml / (m 2 ·1day·1atm) or more, double-sided adhesive sheet; (Measurement method) The thickness of the double-sided PSA sheet was set to 200 μm, and 20 μm-thick unstretched polypropylene films (CPP) were attached to both sides of the sheet to produce a laminated sheet with a layer structure of "CPP (20 μm) / double-sided sheet (adhesive layer 200 μm) / CPP (20 μm)". The oxygen permeability of the laminated sheet was measured using an oxygen permeability measuring device under an environment of 23°C, relative humidity 50%, and 1 atm. 2 The oxygen permeability (PL Similarly, the oxygen permeability (P P ) and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P · · Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2) [2] The double-sided pressure-sensitive adhesive sheet according to [1], wherein the (meth)acrylic copolymer contains (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms, (a2) units derived from a methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms, and (a3) units derived from a hydroxyl group-containing (meth)acrylate. [3] The double-sided pressure-sensitive adhesive sheet according to [1] or [2], wherein the content of the organotin compound (D) is 0.001 to 0.5 parts by mass per 100 parts by mass of the (meth)acrylic copolymer (A). [4] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [3], wherein the content of the monofunctional (meth)acrylic acid ester monomer (B1) is 0.1 to 10 parts by mass and the content of the bifunctional (meth)acrylic acid ester monomer (B2) is 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (A). [5] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [4], which has a total light transmittance of 80% or more. [6] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [5], which has a gel fraction of 75 mass % or less. [7] A laminate comprising the double-sided pressure-sensitive adhesive sheet according to any one of [1] to [6] and a copper mesh-based transparent conductive film. [8] A display device comprising the double-sided pressure-sensitive adhesive sheet according to any one of [1] to [6] and a copper mesh-based transparent conductive film. [Effects of the Invention]
[0009] According to the present invention, even when a pressure-sensitive adhesive sheet is attached to a copper mesh-based transparent conductive film, the copper mesh can be prevented from becoming visible, thereby enabling the manufacture of a display device with excellent visibility and design. [Brief explanation of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of the cross section of the configuration of the double-sided pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0011] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In this specification, "(meth)acrylate" means acrylate or methacrylate.
[0012] (double-sided adhesive sheet) The present invention relates to a double-sided pressure-sensitive adhesive sheet obtained by photocuring a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having reactive functional groups linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, a photopolymerization initiator (C) other than a hydrogen abstraction polymerization initiator, and an organotin compound (D). The oxygen permeability of the double-sided pressure-sensitive adhesive sheet, measured and calculated by the following measurement method, is 2000 ml / (m 2 ·1day·1atm) or higher. (Measurement method) The thickness of the double-sided PSA sheet was set to 200 μm, and 20 μm-thick unstretched polypropylene films (CPP) were attached to both sides of the sheet to produce a laminated sheet with a layer structure of "CPP (20 μm) / double-sided PSA sheet (adhesive layer 200 μm) / CPP (20 μm)". The oxygen permeability of the laminated sheet was measured using an oxygen permeability measuring device under an environment of 23°C, relative humidity 50%, and 1 atm. 2 The oxygen permeability (P L Similarly, the oxygen permeability (P P ) was calculated, and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P · · Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2)
[0013] When preparing a laminate sheet with a layer structure of "unstretched polypropylene (thickness 20 μm) / adhesive layer (thickness 200 μm) / unstretched polypropylene (thickness 20 μm)", 20 μm unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Chemicals Co., Ltd.) is laminated to both sides of a 200 μm thick double-sided adhesive sheet using a hand roller to prepare a laminate sheet. The oxygen permeability (P L ) is measured using an oxygen permeability measuring device. Next, the oxygen permeability (P P The oxygen permeability (P) of the laminated sheet thus obtained is measured using an oxygen permeability measuring device. L ) and oxygen permeability of unstretched polypropylene film (P P) and the oxygen permeability (P A ) can be calculated. A ) is the sheet area of 1m 2 It represents the amount of oxygen that permeates a double-sided adhesive sheet (adhesive layer) per 24 hours (1 day) under a pressure of 1 atm (= 1 atmosphere). When measuring oxygen permeability using an oxygen permeability measuring device, the amount of oxygen permeated is measured in the measurement area specified by the device under an environment of 23°C, relative humidity 50%, and 1 atm. Then, from the measured amount of oxygen, the amount of oxygen permeated per 1 m 2 The oxygen permeability is calculated by converting the amount of oxygen transmitted over 24 hours. For measuring the oxygen permeability, it is preferable to use an oxygen permeability measuring device conforming to ASTM F2622. For example, an oxygen permeability measuring device (OX-TRAN2 / 12 manufactured by MOCON) can be used. When this device (OX-TRAN2 / 12) is used, the measurement area (test cell area) is 50 cm. 2 It can be measured by
[0014] The oxygen permeability (P A ) is 2000ml / (m 2 1 day 1 atm) or more is sufficient, 2050 ml / (m 2 ·1day·1atm) or more is more preferable, and 2100ml / (m 2 ·1day·1atm) or more is more preferable, and 2150ml / (m 2 The upper limit of the oxygen permeability is not particularly limited, but is preferably 30,000 ml / (m 2 In the present invention, the oxygen permeability (P A) is intentionally increased to a predetermined value or more, it is possible to suppress the reduction of the components constituting the blackened film laminated on the copper mesh, and it is presumed that this makes it possible to suppress discoloration of the blackened film. As a result, it is possible to suppress the visualization of the copper mesh. In this embodiment, by appropriately selecting each component constituting the pressure-sensitive adhesive composition, it is possible to suppress the above-mentioned oxygen permeability (P A ) is achieved.
[0015] In this embodiment, the oxygen permeability (P A By setting the above range, for example, the amount of oxygen present in the vicinity of the blackened film of the copper mesh can be made equal to or greater than a certain level. In this case, it is presumed that extraction and reduction of oxygen in the blackened film can be suppressed, thereby suppressing discoloration.
[0016] The double-sided pressure-sensitive adhesive sheet of this embodiment is preferably composed only of a pressure-sensitive adhesive layer, but may also have a support. In this case, examples of the support include plastic films such as polystyrene, styrene-acrylic copolymer, acrylic resin, polyethylene terephthalate, polycarbonate, polyether ether ketone, and triacetyl cellulose; and optical films such as anti-reflection films and electromagnetic wave shielding films. When the double-sided pressure-sensitive adhesive sheet has a support, the gel fraction described below refers to the gel fraction of the pressure-sensitive adhesive layer. When the double-sided pressure-sensitive adhesive sheet is a pressure-sensitive adhesive sheet, it may be a sheet composed of multiple pressure-sensitive adhesive layers, but is preferably a pressure-sensitive adhesive sheet composed of a single pressure-sensitive adhesive layer.
[0017] The application of the double-sided pressure-sensitive adhesive sheet of this embodiment is not particularly limited, but is preferably used for bonding copper mesh-based transparent conductive films, as this can suppress the visualization of the copper mesh. The copper mesh preferably has a blackened film. The blackened film is formed by a blackening treatment, in which an anti-reflective black coating is formed on the copper mesh. Examples of blackened films include films containing copper oxide (CuO) and copper oxynitride (CuNO). The blackened film is not particularly limited as long as it can suppress the reflectance of the copper mesh, and known blackened films can be used, such as films containing black pigments. In the blackening treatment, a copper oxide film or copper oxynitride film can be formed on the copper mesh by sputtering or other known methods. Furthermore, the blackening treatment may involve electrodeposition coating of a black pigment.
[0018] In particular, the blackened film is preferably a copper oxide film or a copper oxynitride film. In this case, the double-sided pressure-sensitive adhesive sheet of this embodiment is preferably for bonding a copper mesh-based transparent conductive film with a copper oxide film or a copper mesh-based transparent conductive film with a copper oxynitride film.
[0019] The double-sided pressure-sensitive adhesive sheet of this embodiment can also be used as a component of a general display device or optical device.
[0020] The thickness of the double-sided pressure-sensitive adhesive sheet of this embodiment can be appropriately set depending on the application and is not particularly limited. Typically, the thickness of the double-sided pressure-sensitive adhesive sheet is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. Furthermore, the thickness of the double-sided pressure-sensitive adhesive sheet is preferably 1000 μm or less, more preferably 800 μm or less, even more preferably 600 μm or less, even more preferably 500 μm or less, and particularly preferably 400 μm or less. By setting the thickness of the double-sided pressure-sensitive adhesive sheet within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet can be easily increased. Furthermore, by setting the thickness of the double-sided pressure-sensitive adhesive sheet within the above range, sufficient conformability to uneven surfaces can be ensured, and durability can be further improved.
[0021] The total light transmittance of the double-sided pressure-sensitive adhesive sheet is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the double-sided pressure-sensitive adhesive sheet may be 100%. By adjusting the total light transmittance of the double-sided pressure-sensitive adhesive sheet to fall within the above range, transparency can be increased, making it suitable for use in optical applications such as display devices. The total light transmittance is a value measured in accordance with JIS K 7361-1:1997 in an environment of 23°C and relative humidity of 50%.
[0022] The haze of the double-sided pressure-sensitive adhesive sheet is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less. The lower limit of the haze value of the double-sided pressure-sensitive adhesive sheet is not particularly limited and may be 0%. By keeping the haze of the double-sided pressure-sensitive adhesive sheet within the above range, transparency can be improved, making it suitable for optical applications such as display devices. The haze is a value measured in accordance with JIS K 7136:2000 in an environment of 23°C and relative humidity of 50%.
[0023] The gel fraction of the double-sided pressure-sensitive adhesive sheet is preferably 0% by mass or more, more preferably 10% by mass or more, more preferably 40% by mass or more, and particularly preferably 50% by mass or more. Furthermore, the gel fraction of the double-sided pressure-sensitive adhesive sheet is preferably 75% by mass or less, more preferably 70% by mass or less. By ensuring that the gel fraction of the double-sided pressure-sensitive adhesive sheet is within the above range, it becomes easier to control the oxygen permeability of the double-sided pressure-sensitive adhesive sheet within a predetermined numerical range. Furthermore, by ensuring that the gel fraction of the double-sided pressure-sensitive adhesive sheet is within the above range, it is possible to improve the conformability to uneven surfaces.
[0024] The adhesive strength of the double-sided pressure-sensitive adhesive sheet to glass is preferably 2 N / 10 mm or more, more preferably 5 N / 10 mm or more. Furthermore, the adhesive strength of the double-sided pressure-sensitive adhesive sheet to glass is preferably 25 N / 10 mm or less, more preferably 20 N / 10 mm or less. By keeping the adhesive strength of the double-sided pressure-sensitive adhesive sheet above the above range, unintended peeling does not occur, while by keeping it below the above range, it can be easily peeled off in the event of incorrect application or when dismantling the panel for recycling. The adhesive strength of the double-sided pressure-sensitive adhesive sheet described above is the value of the adhesive strength to glass measured in accordance with the adhesive strength measurement method specified in JIS Z 0237, using a 100 μm thick polyethylene terephthalate (PET) film backed on one side of the double-sided pressure-sensitive adhesive sheet and soda glass as the adherend.
[0025] (Adhesive composition) The double-sided pressure-sensitive adhesive sheet of this embodiment is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, and a photopolymerization initiator (C) excluding hydrogen abstraction polymerization initiators.
[0026] ((Meth)acrylic copolymer (A)) The (meth)acrylic copolymer (A) preferably has a transparency sufficient to not impair the visibility of a display device, and preferably has a unit derived from a (meth)acrylate. In this specification, the term "unit" refers to a repeating unit (monomer unit) that constitutes a polymer.
[0027] The (meth)acrylic copolymer (A) preferably contains (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms, (a2) units derived from a methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms, and (a3) units derived from a hydroxyl group-containing (meth)acrylate. Furthermore, the content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 15 to 79.5 mass%, the content of (a2) units derived from a methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 20 to 79.5 mass%, and the content of (a3) units derived from a hydroxyl group-containing (meth)acrylate is preferably 0.5 to 15 mass%, relative to the total mass of the (meth)acrylic copolymer. In this embodiment, the use of a (meth)acrylic copolymer having specific structural units makes it easy to achieve an oxygen permeability of the double-sided pressure-sensitive adhesive sheet of a predetermined value or higher. This makes it difficult for the blackened film on the copper mesh of the transparent conductive film to be reduced, effectively preventing discoloration. In addition, in this embodiment, the cohesive force of the pressure-sensitive adhesive is increased by using a (meth)acrylic copolymer having a specific structural unit, and a pressure-sensitive adhesive sheet with excellent adhesive properties and durability can be obtained.
[0028] -(a1) a unit derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms- (a1) Examples of acrylates having a linear or branched alkyl group having 1 to 10 carbon atoms include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, octyl acrylate, isooctyl acrylate, isononyl acrylate, isodecyl acrylate, and 2-ethylhexyl acrylate. These may be used alone or in combination of two or more. Among these, the (meth)acrylic copolymer preferably contains units derived from an acrylate having a branched alkyl group having 1 to 10 carbon atoms, and more preferably contains units derived from an acrylate having a branched alkyl group having 4 to 10 carbon atoms. As the units derived from such acrylates having a branched alkyl group, units derived from 2-ethylhexyl acrylate (2EHA) are preferred. In addition, in the present embodiment, the (meth)acrylic copolymer preferably contains units derived from an acrylate having a branched alkyl group with 1 to 10 carbon atoms and units derived from an acrylate having a linear alkyl group with 1 to 10 carbon atoms, and more preferably contains units derived from an acrylate having a branched alkyl group with 4 to 10 carbon atoms and units derived from an acrylate having a linear alkyl group with 1 to 5 carbon atoms.
[0029] The content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 15% by mass or more, and more preferably 20% by mass or more, based on the total mass of the (meth)acrylic copolymer. Furthermore, the content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 79.5% by mass or more, and more preferably 70% by mass or less, based on the total mass of the (meth)acrylic copolymer. By keeping the content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms within the above range, it is possible to obtain a pressure-sensitive adhesive sheet that can exhibit excellent adhesive strength and have an oxygen permeability of a predetermined value or more, thereby suppressing visualization of the copper mesh.
[0030] -(a2) a unit derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms- (a2) Examples of methacrylates having a linear or branched alkyl group having 1 to 10 carbon atoms include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, octyl methacrylate, isooctyl methacrylate, isononyl methacrylate, isodecyl methacrylate, and 2-ethylhexyl methacrylate. These may be used alone or in combination of two or more. Among these, the (meth)acrylic copolymer preferably contains units derived from a methacrylate having a branched alkyl group having 1 to 10 carbon atoms, and more preferably contains units derived from a methacrylate having a branched alkyl group having 4 to 10 carbon atoms. As the units derived from such methacrylates having a branched alkyl group, units derived from 2-ethylhexyl methacrylate (2EHMA) are preferred. In addition, in the present embodiment, the (meth)acrylic copolymer preferably contains units derived from a methacrylate having a branched alkyl group with 1 to 10 carbon atoms and units derived from a methacrylate having a linear alkyl group with 1 to 10 carbon atoms, and more preferably contains units derived from a methacrylate having a branched alkyl group with 4 to 10 carbon atoms and units derived from a methacrylate having a linear alkyl group with 1 to 5 carbon atoms.
[0031] It is preferable that the alkyl groups in (a1) the acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms and (a2) the methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms are the same type.
[0032] The content of (a2) units derived from methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 20% by mass or more, and more preferably 25% by mass or more, based on the total mass of the (meth)acrylic copolymer. Furthermore, the content of (a2) units derived from methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 79.5% by mass or more, and more preferably 75% by mass or less, based on the total mass of the (meth)acrylic copolymer. By keeping the content of (a2) units derived from methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms within the above range, it is possible to obtain a pressure-sensitive adhesive sheet that can exhibit excellent adhesive strength and have an oxygen permeability of a predetermined value or more, thereby suppressing visualization of the copper mesh.
[0033] -(a3) Units derived from hydroxyl group-containing (meth)acrylate- (a3) Examples of hydroxyl group-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and polyalkylene glycol mono(meth)acrylate. These may be used alone or in combination of two or more. Among these, at least one selected from 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate is preferably used.
[0034] The content of units derived from (a3) hydroxyl group-containing (meth)acrylate is preferably 0.5% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on the total mass of the (meth)acrylic copolymer. Furthermore, the content of units derived from (a3) hydroxyl group-containing (meth)acrylate is preferably 15% by mass or less, more preferably 13% by mass or less, based on the total mass of the (meth)acrylic copolymer. By keeping the content of units derived from (a3) hydroxyl group-containing (meth)acrylate within the above ranges, excellent adhesive strength can be exhibited, and the oxygen permeability and gel fraction of the adhesive sheet can be easily controlled.
[0035] -Other monomer units- The (meth)acrylic copolymer may contain other monomer units in addition to those mentioned above. Examples of such other monomers include (meth)acrylic acid ester units having a cyclic group, such as cyclohexyl (meth)acrylate and benzyl (meth)acrylate, as well as (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinylpyrrolidone, and vinylpyridine. The content of such other monomer units in the (meth)acrylic copolymer is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less.
[0036] -Physical properties of (meth)acrylic copolymer- The weight-average molecular weight of the (meth)acrylic copolymer is preferably 100,000 or more, more preferably 200,000 or more. The weight-average molecular weight of the (meth)acrylic copolymer is preferably 3,000,000 or less, more preferably 2,000,000 or less. By setting the weight-average molecular weight within the above range, it becomes easier to control the oxygen permeability of the pressure-sensitive adhesive sheet to a predetermined value or higher, and sufficient conformability to uneven surfaces can be ensured. The weight-average molecular weight of the (meth)acrylic copolymer is the weight-average molecular weight of the (meth)acrylic copolymer contained in the pressure-sensitive adhesive composition. The weight-average molecular weight is measured by gel permeation chromatography (GPC) and is a value determined using polystyrene as a standard.
[0037] (Monofunctional (meth)acrylic acid ester monomer (B1)) The monofunctional (meth)acrylic acid ester monomer (B1) is a monomer having one reactive double bond in the molecule and having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms. Examples of the monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms include isobornyl (meth)acrylate, isostearyl (meth)acrylate, stearyl acrylate (meth)acrylate, lauryl (meth)acrylate, isodecyl (meth)acrylate, cetyl (meth)acrylate, isomyristyl (meth)acrylate, undeca(meth)acrylate, tridecyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. Among them, the monofunctional (meth)acrylic acid ester monomer (B1) is preferably at least one selected from the group consisting of isobornyl (meth)acrylate, isostearyl (meth)acrylate, and lauryl (meth)acrylate. Commercially available examples of the monofunctional (meth)acrylic acid ester monomer (B1) include IBXA manufactured by Osaka Organic Chemical Industry Ltd., ISTA manufactured by Osaka Organic Chemical Industry Ltd., and LA manufactured by Osaka Organic Chemical Industry Ltd.
[0038] In this embodiment, by using a monomer having a carbon number within a predetermined range as the monofunctional (meth)acrylic acid ester monomer (B1), a loose network structure can be formed in the double-sided PSA sheet, which allows the oxygen permeability of the double-sided PSA sheet to be within a predetermined range, thereby suppressing discoloration of the blackened film on the copper mesh and preventing visualization of the copper mesh.
[0039] In the pressure-sensitive adhesive composition, the content of the monofunctional (meth)acrylic acid ester monomer (B1) relative to 100 parts by mass of the (meth)acrylic copolymer (A) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more. Furthermore, the content of the monofunctional (meth)acrylic acid ester monomer (B1) is preferably 10 parts by mass or less. By ensuring that the content of the monofunctional (meth)acrylic acid ester monomer (B1) is within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet can be set within a predetermined range, thereby suppressing discoloration of the blackened film on the copper mesh and preventing visualization of the copper mesh.
[0040] (Bifunctional (meth)acrylic acid ester monomer (B2)) The bifunctional (meth)acrylic acid ester monomer (B2) has two reactive functional groups. The two reactive functional groups are linked by a linking group derived from a linear diol having 4 to 12 carbon atoms. The two reactive functional groups are more preferably linked by a linking group derived from a linear diol having 6 to 12 carbon atoms, and even more preferably linked by a linking group derived from a linear diol having 6 to 10 carbon atoms.
[0041] The bifunctional (meth)acrylic acid ester monomer (B2) is preferably one represented by the following structural formula: [ka]
[0042] In the above formula, R1 and R2 each independently represent a hydrogen atom or a methyl group, preferably a hydrogen atom. R represents a linear alkylene group having 4 to 12 carbon atoms, preferably an alkylene group having 6 to 12 carbon atoms, and more preferably an alkylene group having 6 to 10 carbon atoms.
[0043] Examples of the bifunctional (meth)acrylic acid ester monomer (B2) in which reactive functional groups are linked by a linking group derived from a linear diol having 4 to 12 carbon atoms include 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, and 1,10-decanediol diacrylate. Among these, the bifunctional (meth)acrylic acid ester monomer (B2) is preferably at least one selected from the group consisting of 1,6-hexanediol diacrylate and 1,10-decanediol diacrylate. Commercially available examples of the bifunctional (meth)acrylic acid ester monomer (B2) include A-HD-N, A-NOD-N, and A-DOD-N manufactured by Shin-Nakamura Chemical Co., Ltd.
[0044] In this embodiment, by using a bifunctional (meth)acrylic acid ester monomer (B2) in which a reactive functional group is linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, the oxygen permeability (P A ) can be more easily controlled than desired, and as a result, visualization of the copper mesh can be effectively suppressed when a pressure-sensitive adhesive sheet is attached to a copper mesh-based transparent conductive film. This is thought to be because the two reactive functional groups are linked by a linear diol having 4 to 12 carbon atoms, which has high structural flexibility, thereby increasing the flexibility of the (meth)acrylic copolymer (A), which is the base polymer.
[0045] In this embodiment, by using the bifunctional (meth)acrylic acid ester monomer (B2) as described above, the crosslink density of the polymer in the double-sided PSA sheet can be controlled, and a loose mesh structure can be formed, which allows the oxygen permeability of the double-sided PSA sheet to be within a predetermined range, thereby suppressing discoloration of the blackened film on the copper mesh and preventing visualization of the copper mesh.
[0046] The content of the bifunctional (meth)acrylic acid ester monomer (B2) in the pressure-sensitive adhesive composition relative to 100 parts by mass of the (meth)acrylic copolymer (A) is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more. Furthermore, the content of the bifunctional (meth)acrylic acid ester monomer (B2) is preferably 5 parts by mass or less. By ensuring that the content of the bifunctional (meth)acrylic acid ester monomer (B2) is within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet can be set within a predetermined range, thereby suppressing discoloration of the blackened film on the copper mesh and preventing visualization of the copper mesh.
[0047] (Photopolymerization initiator (C)) The photopolymerization initiator (C) initiates polymerization of the polyfunctional monomer by irradiation with active energy rays. Here, "active energy rays" refers to electromagnetic waves or charged particle rays that have an energy quantum, and examples thereof include ultraviolet rays, electron beams, visible light, X-rays, and ion beams. Among these, ultraviolet rays or electron beams are preferred from the viewpoint of versatility, and ultraviolet rays are particularly preferred.
[0048] The photopolymerization initiator (C) used in this embodiment is a photopolymerization initiator other than a hydrogen abstraction type polymerization initiator. By using a photopolymerization initiator other than a hydrogen abstraction type polymerization initiator, discoloration of the blackened layer can be more effectively suppressed.
[0049] Examples of the photopolymerization initiator (C) include hydroxyalkylphenone-based photopolymerization initiators such as 1-hydroxycyclohexyl phenyl ketone; acetophenone-based photopolymerization initiators such as 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-[4-(2-hydroxyethoxyl)-phenyl]-2-hydroxy-methylpropanone, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methyl-1-propanone; acylphosphine oxide-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoyl)phenylphosphine oxide; and oil-soluble polymerization initiators such as oxime ester-based photopolymerization initiators and cationic photopolymerization initiators. Among these, the photopolymerization initiator is preferably at least one selected from the group consisting of hydroxyalkylphenone-based photopolymerization initiators and acylphosphine oxide-based photopolymerization initiators.
[0050] Commercially available photopolymerization initiators (C) include Omnirad819 and Omnirad184 manufactured by IGM Resins BV.
[0051] The content of the photopolymerization initiator (C) in the pressure-sensitive adhesive composition is preferably 0.01 parts by mass or more, and more preferably 0.05 parts by mass or more, per 100 parts by mass of the (meth)acrylic copolymer. Furthermore, the content of the photopolymerization initiator (C) in the pressure-sensitive adhesive composition is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the (meth)acrylic copolymer. By keeping the content of the photopolymerization initiator within the above range, the hardness of the double-sided pressure-sensitive adhesive sheet can be increased, and the durability, processability, and adhesion of the double-sided pressure-sensitive adhesive sheet can be improved.
[0052] (Organotin compounds (D)) The PSA composition contains an organotin compound (D). Examples of the organotin compound (D) include dimethyltin dichloride, dimethyltin dilaurate, dimethyltin di(2-ethylhexanoate), dimethyltin diacetate, dibutyltin dilaurate, dihexyltin diacetate, dioctyltin dilaurate, dibutyltin diacetylacetonate, dibutyltin diacetate, dibutyltin dioctoate, dioctyltin diacetylacetonate, dioctyltin diketanoate, dioctylstannoxane, dioctyltin dicarboxylate, dioctyltin oxide, dimethyltin bis(isooctylthioglycolate) salt, dioctyltin bis(isooctylthioglycolate) salt, tin octoate, and tin decanoate. Among them, it is preferable to use at least one selected from dioctyltin dilaurate and dioctyltin oxide as the organotin compound, and it is more preferable to use dioctyltin dilaurate.
[0053] In this embodiment, the content of the organotin compound (D) contained in the pressure-sensitive adhesive composition is preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, even more preferably 0.3 parts by mass or less, even more preferably 0.2 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer. The content of the organotin compound (D) contained in the pressure-sensitive adhesive composition is preferably 0.001 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer. By setting the content of the organotin compound (D) contained in the pressure-sensitive adhesive composition within the above range, the blackened film on the copper mesh of the transparent conductive film is less likely to be reduced, effectively preventing discoloration and preventing the copper mesh from becoming visible.
[0054] (solvent) The PSA composition may further contain a solvent, which is used to improve the coatability of the PSA composition.
[0055] Examples of such solvents include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; and polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and derivatives thereof.
[0056] The solvent may be used alone or in combination of two or more. The content of the solvent in the pressure-sensitive adhesive composition is not particularly limited, but may be 25 to 500 parts by mass, or 30 to 400 parts by mass, per 100 parts by mass of the (meth)acrylic copolymer. The content of the solvent may be 10 to 90% by mass, or 20 to 80% by mass, relative to the total mass of the pressure-sensitive adhesive composition.
[0057] (optional ingredient) In this embodiment, the pressure-sensitive adhesive composition may contain optional components such as those listed below, depending on the application and required properties. However, it is preferable that the pressure-sensitive adhesive composition is substantially free of a crosslinking agent. Specifically, the content of the crosslinking agent in the pressure-sensitive adhesive composition is preferably 0.1 mass % or less. When the content of the crosslinking agent in the pressure-sensitive adhesive composition is within the above range, it can be said that the pressure-sensitive adhesive composition is substantially free of a crosslinking agent.
[0058] Examples of optional components include silane coupling agents, plasticizers, antioxidants, metal corrosion inhibitors, tackifiers, polymerization initiators, polymerizable monomers, ultraviolet absorbers, etc. In this case, the content of the optional components is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, still more preferably 0.5 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer.
[0059] As the silane coupling agent, for example, a reactive functional group-containing silane coupling agent can be used. Examples include mercapto-based silane coupling agents, (meth)acrylic silane coupling agents, isocyanate-based silane coupling agents, epoxy-based silane coupling agents, and amino-based silane coupling agents. Examples of mercapto-based silane coupling agents include mercaptoalkoxysilane compounds (e.g., mercapto group-substituted alkoxy oligomers), but as described below, attention must be paid to the content. Other reactive functional group-containing silane coupling agents include those described in
[0094] to
[0096] of JP 2020-114914 A.
[0060] The plasticizer may include, for example, a non-functional acrylic polymer. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, lactone-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. The metal corrosion inhibitor may include a benzotriazole-based resin. Examples of tackifiers include rosin-based resins, terpene-based resins, terpene-phenol-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, petroleum resins, and methacrylic resins. Examples of ultraviolet absorbers include benzotriazole-based compounds and benzophenone-based compounds.
[0061] It is also preferred that the pressure-sensitive adhesive composition of the present embodiment does not contain any of the optional components described above, and contains, as solid contents, only the (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, a photopolymerization initiator (C) excluding hydrogen abstraction polymerization initiators, and an organotin compound (D).
[0062] (Double-sided adhesive sheet with release sheet) A release sheet is preferably attached to at least one surface of the double-sided PSA sheet of this embodiment. This embodiment also relates to a double-sided PSA sheet with a release sheet. The release sheet is peeled off from the double-sided PSA sheet when the double-sided PSA sheet is used.
[0063] Figure 1 is a cross-sectional view showing an example of the configuration of a double-sided pressure-sensitive adhesive sheet with a release sheet. The double-sided pressure-sensitive adhesive sheet 1 shown in Figure 1 has release sheets 12 (12a, 12b) on both sides of a pressure-sensitive adhesive layer 11. The double-sided pressure-sensitive adhesive sheet in Figure 1 is a non-carrier type single-layer pressure-sensitive adhesive sheet, and is a double-sided pressure-sensitive adhesive sheet.
[0064] Examples of the release sheet include a release laminate sheet having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low-polarity substrate. The substrate for the release sheet in the release laminate sheet is paper or a polymer film. The release agent constituting the release agent layer is, for example, a general-purpose addition-type or condensation-type silicone-based release agent or a long-chain alkyl group-containing compound. In particular, an addition-type silicone-based release agent, which has high reactivity, is preferably used. Specific examples of silicone-based release agents include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd., and KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, silicone-based release agents containing SiO2 units and (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 It is preferable to contain a silicone resin, which is an organosilicon compound having a unit. Specific examples of silicone resins include BY24-843, SD-7292, and SHR-1404 manufactured by Dow Corning Toray Silicone Co., Ltd., and KS-3800 and X92-183 manufactured by Shin-Etsu Chemical Co., Ltd.
[0065] In order to facilitate peeling of the release sheet 12, it is preferable that the releasability of the release sheet 12a and the release sheet 12b be different. In other words, if the releasability from one side is different from the releasability from the other side, it becomes easy to peel off only the release sheet 12 with the higher releasability first. In this case, the releasability of the release sheet 12 between the release sheet 12a and the release sheet 12b may be adjusted depending on the lamination method and lamination order.
[0066] (Manufacturing method of double-sided pressure-sensitive adhesive sheet) The manufacturing process for the double-sided PSA sheet of this embodiment preferably includes a step of applying a PSA composition to a release sheet to form a coating film. Hereinafter, the step of applying a PSA composition to a release sheet to form a coating film will be described as a representative example.
[0067] The PSA composition for forming the PSA sheet can be applied using a known coating device, such as a blade coater, air knife coater, roll coater, bar coater, gravure coater, microgravure coater, rod blade coater, lip coater, die coater, curtain coater, etc. The coating film can be heated using a known heating device, such as a heating furnace or an infrared lamp.
[0068] This embodiment includes a step of photocuring the coating film. That is, the double-sided pressure-sensitive adhesive sheet of this embodiment is a photocurable double-sided pressure-sensitive adhesive sheet. Examples of light used for light irradiation include ultraviolet light and visible light. Of these, ultraviolet light with a wavelength of 250 to 400 nm is preferably used. The ultraviolet irradiation conditions are an irradiance of 0.1 mW / cm when measured with an ultraviolet illuminance meter with spectral sensitivity centered on a wavelength of 365 nm. 2 The light intensity is 500mJ / cm 2 The above is desirable. By adopting such ultraviolet irradiation conditions, a pressure-sensitive adhesive sheet with a high gel fraction and excellent durability can be obtained. As the light source, ultraviolet fluorescent lamps such as chemical lamps and black lamps, high-pressure mercury lamps, low-pressure mercury lamps, ultra-high-pressure mercury lamps, mercury-xenon lamps, metal halide lamps, LED lamps, carbon arcs, xenon arcs, etc. can be used.
[0069] In the process of photo-curing the coating, the cumulative amount of ultraviolet light irradiated is 500 mJ / cm 2 It is preferable that the concentration is 1000 mJ / cm or more. 2 More preferably, it is 1500 mJ / cm or more. 2 The cumulative dose of the irradiated ultraviolet light is more preferably 20,000 mJ / cm 2 or more. 2 It is preferable that:
[0070] The double-sided pressure-sensitive adhesive sheet of this embodiment is completely cured by a photo-curing process. The cumulative dose of ultraviolet light required for complete curing varies depending on the components contained in the pressure-sensitive adhesive composition. For example, the cumulative dose of ultraviolet light irradiated is 3000 mJ / cm. 2 That is, the double-sided pressure-sensitive adhesive sheet of this embodiment is a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched, or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having reactive functional groups linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, and a photopolymerization initiator (C) other than a hydrogen abstraction polymerization initiator, and is exposed to an integrated light dose of 3000 mJ / cm. 2This double-sided pressure-sensitive adhesive sheet is photocured by irradiating it with ultraviolet light so that the adhesive becomes
[0071] Before the step of photo-curing the coating film, a step of drying the coating film may be carried out as necessary. The temperature in the drying step is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher. The temperature in the drying step is preferably 150°C or lower. The processing time in the drying step is preferably 10 seconds or longer, more preferably 1 minute or longer. The processing time in the drying step is preferably 1 hour or shorter.
[0072] (How to use the adhesive sheet) In a method of using the double-sided pressure-sensitive adhesive sheet of this embodiment, one release sheet of the double-sided pressure-sensitive adhesive sheet with a release sheet is peeled off and the sheet is brought into contact with a copper mesh-based transparent conductive film for bonding, and then the other release sheet is peeled off and the sheet is brought into contact with another adherend. If the pressure-sensitive adhesive sheet is a semi-cured pressure-sensitive adhesive sheet that contains a polymerization initiator and is post-curable, the pressure-sensitive adhesive layer may be completely cured by irradiating it with active energy rays in this state.
[0073] (Laminate / Display Device) This embodiment may relate to a laminate including the above-described double-sided pressure-sensitive adhesive sheet and a copper mesh-based transparent conductive film. For example, in the laminate of this embodiment, it is preferable that a copper mesh-based transparent conductive film is laminated on one side of the double-sided pressure-sensitive adhesive sheet, and another adherend is laminated on the other side of the double-sided pressure-sensitive adhesive sheet. It is preferable that the double-sided pressure-sensitive adhesive sheet is directly attached to the side of the copper mesh-based transparent conductive film on which the copper mesh is formed.
[0074] This embodiment may also relate to a display device including the above-described double-sided pressure-sensitive adhesive sheet and a copper mesh-based transparent conductive film. For example, in the display device of this embodiment, it is preferable that a copper mesh-based transparent conductive film is laminated on one side of the double-sided pressure-sensitive adhesive sheet, and another adherend is laminated on the other side of the double-sided pressure-sensitive adhesive sheet. It is preferable that the double-sided pressure-sensitive adhesive sheet is directly attached to the side of the copper mesh-based transparent conductive film on which the copper mesh is formed.
[0075] Other adherends include, for example, optical components constituting display devices, and examples of optical components include various components in optical products such as touch panels and image display devices. Examples of components for touch panels include hard coat films, fingerprint-resistant films, and cover films. Examples of components for image display devices include anti-reflection films, alignment films, polarizing films, retardation films, and brightness enhancement films used in liquid crystal display devices. Examples of materials used for these components include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymers, triacetyl cellulose, polyimide, and cellulose acylate.
[0076] [Method of manufacturing laminate] The method for producing a laminate according to the present embodiment preferably includes a step of applying pressure to the surface of the copper mesh-based transparent conductive film that is in contact with the copper mesh while the double-sided pressure-sensitive adhesive sheet according to the present embodiment is in contact with the surface. In this case, degassing may be performed by applying pressure, or a degassing step may be performed before or after the pressure-applying step. The pressure-applying step may also be performed while heating is being performed, or a heating step may also be performed before or after the pressure-applying step. For example, the double-sided pressure-sensitive adhesive sheet may be brought into contact with the copper mesh-based transparent conductive film, and then pressurized, heated, and degassed in this state using an autoclave or the like, or pressure and vacuum degassing may be performed in this state to improve adhesion. [Example]
[0077] The features of the present invention will be explained in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, treatment contents, treatment procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be construed as being limited by the specific examples shown below.
[0078] [Synthesis example] <Synthesis of (meth)acrylic copolymer A-1> 2-Ethylhexyl acrylate (2EHA) as an acrylate having a branched alkyl group with 1 to 10 carbon atoms, 2-ethylhexyl methacrylate (2EHMA) as a methacrylate having a branched alkyl group with 1 to 10 carbon atoms, and 2-hydroxyethyl methacrylate (2HEMA) as a hydroxyl group-containing (meth)acrylate were blended in a mass ratio of 2EHA:2EHMA:2HEMA = 20:70:10, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent by heating to 60°C. This yielded a solution (a-1) containing a crosslinkable (meth)acrylic copolymer (A-1) with a solids concentration of 50% by mass and a weight-average molecular weight of 480,000.
[0079] <Synthesis of (meth)acrylic copolymer A-2> Methyl acrylate (MA) and 2-ethylhexyl acrylate (2EHA) as acrylates having a linear or branched alkyl group with 1 to 10 carbon atoms, 2-ethylhexyl methacrylate (2EHMA) as a methacrylate having a branched alkyl group with 1 to 10 carbon atoms, and 2-hydroxyethyl acrylate (2HEA) as a hydroxyl group-containing (meth)acrylate were blended in a mass ratio of MA:2EHA:2EHMA:2HEA = 30:35:25:10, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent by heating to 60°C. This resulted in a solution (a-2) containing a crosslinkable (meth)acrylic copolymer (A-2) with a solids concentration of 50% by mass and a weight-average molecular weight of 800,000.
[0080] <Synthesis of (meth)acrylic copolymer A-3> 2-Ethylhexyl acrylate (2EHA) as an acrylate having a branched alkyl group with 1 to 10 carbon atoms, methyl methacrylate (MMA) and 2-ethylhexyl methacrylate (2EHMA) as methacrylates having linear and branched alkyl groups with 1 to 10 carbon atoms, and 2-hydroxyethyl acrylate (2HEA) as a hydroxyl group-containing (meth)acrylate were blended in a mass ratio of 2EHA:MMA:2EHMA:2HEA = 20:10:60:10, and polymerized in the presence of azobisisobutyronitrile (AIBN) in ethyl acetate as a polymerization solvent by heating to 60°C. This yielded a solution (a-3) containing a crosslinkable (meth)acrylic copolymer (A-3) with a solids concentration of 50% by mass and a weight-average molecular weight of 400,000.
[0081] <Synthesis of (meth)acrylic copolymer A-4> Butyl acrylate (BA) as an acrylate having a linear alkyl group with 1 to 10 carbon atoms and 2-hydroxyethyl acrylate (2HEA) as a hydroxyl group-containing (meth)acrylate were mixed in a mass ratio of BA:2HEA = 70:30, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent by heating to 60°C. This yielded a solution (a-4) containing a crosslinkable (meth)acrylic copolymer (A-4) with a solids concentration of 50 mass% and a weight-average molecular weight of 500,000.
[0082] <Weight average molecular weight> The weight average molecular weight of the (meth)acrylic copolymer was measured by gel permeation chromatography (GPC) under the following conditions. Solvent: Tetrahydrofuran Column: Shodex KF801, KF803L, KF800L, KF800D (four columns connected together, manufactured by Showa Denko K.K.) Column temperature: 40℃ Sample concentration: 0.5% by mass Detector: RI-2031plus (JASCO) Pump: RI-2080plus (JASCO) ·Flow rate (flow rate): 0.8ml / min ·Injection volume: 10μl Calibration curve: A calibration curve was used using 10 samples of standard polystyrene Shodex standard polystyrene (manufactured by Showa Denko K.K.) with Mw = 1320 to 2,500,000.
[0083] [Example 1] <Preparation of Pressure-Sensitive Adhesive Composition> To 100 parts by mass of the (meth)acrylic copolymer (A-1) contained in solution (a-1), 5 parts by mass of isobornyl acrylate (IBXA) as a monofunctional (meth)acrylic acid ester monomer (B1) having a cyclic alkyl group with 10 carbon atoms, 1 part by mass of 1,6-hexanediol diacrylate (A-HD-N) as a bifunctional (meth)acrylic acid ester monomer (B2) in which a reactive functional group is linked by a linking group derived from a linear diol with 6 carbon atoms, 0.5 parts by mass of Omnirad819 (manufactured by IGM Resins BV) as a photopolymerization initiator, and 0.02 parts by mass of dioctyltin dilaurate as an organotin compound were added, and the raw materials were added to ethyl acetate so that the concentration of the raw materials was 40% by mass, and the mixture was stirred to prepare a pressure-sensitive adhesive composition.
[0084] <Preparation of double-sided adhesive sheet> The pressure-sensitive adhesive composition prepared as described above was applied uniformly with an applicator to the surface of a 50 μm thick polyethylene terephthalate film (first release sheet, Oji F-Tex Co., Ltd., 50RL-07(2)) equipped with a release agent layer treated with a silicone-based release agent, so as to form a coating film with a coating thickness of 100 μm after drying. The coating film was dried at 80°C for 3 minutes in an air-circulating constant-temperature oven, thereby forming a pressure-sensitive adhesive layer (double-sided pressure-sensitive adhesive sheet of Example 1) on the surface of the first release sheet.
[0085] <Preparation of double-sided adhesive sheet with release sheet> Next, a 38μm thick second release sheet (Oji F-Tex Co., Ltd., 38RL-07(L)) with a different release strength from the first release sheet was laminated to the surface of the adhesive layer, and the sheet was cured for 14 days at 23°C and a relative humidity of 50%. This resulted in a double-sided adhesive sheet with release sheets, in which the adhesive layer (adhesive sheet) was sandwiched between a pair of release sheets with different release strengths, with a first release sheet / double-sided adhesive sheet / second release sheet configuration. Next, a high-pressure mercury lamp was used to illuminate the second release sheet side of this adhesive sheet with release sheet, with an integrated light intensity of 3000mJ / cm. 2 Thus, a photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained.
[0086] [Example 2] A photocured double-sided PSA sheet with a release sheet was obtained using the same procedure as in Example 1, except that the solution (a-1) of (meth)acrylic copolymer (A-1) was changed to solution (a-2) of (meth)acrylic copolymer (A-2), isobornyl acrylate (IBXA) was changed to isostearyl acrylate (ISTA), a monofunctional (meth)acrylic acid ester monomer having a branched alkyl group with 18 carbon atoms, and dioctyltin dilaurate was changed to dioctyltin oxide.
[0087] [Example 3] A photocured double-sided PSA sheet with a release sheet was obtained using the same procedure as in Example 1, except that solution (a-1) of (meth)acrylic copolymer (A-1) was changed to solution (a-3) of (meth)acrylic copolymer (A-3), isobornyl acrylate (IBXA) was changed to lauryl acrylate (LA), a monofunctional (meth)acrylic acid ester monomer having a linear alkyl group with 12 carbon atoms, 1,6-hexanediol diacrylate (A-HD-N) was changed to 1,10-decanediol diacrylate (A-DOD-N), a bifunctional (meth)acrylic acid ester monomer in which reactive functional groups are linked by a linking group derived from a linear diol with 10 carbon atoms, and the photopolymerization initiator Omnirad819 (manufactured by IGM Resins BV) was changed from 0.5 parts by mass to 1.0 parts by mass of Omnirad184 (manufactured by IGM Resins BV).
[0088] [Example 4] A photocured double-sided PSA sheet with a release sheet was obtained using the same procedure as in Example 1, except that isobornyl acrylate (IBXA) was changed to isostearyl acrylate (ISTA), a monofunctional (meth)acrylic acid ester monomer with a branched alkyl chain containing 18 carbon atoms, 1,6-hexanediol diacrylate (A-HD-N) was changed to 1,10-decanediol diacrylate (A-DOD-N), a bifunctional (meth)acrylic acid ester monomer in which the functional group is linked by a linear diol containing 10 carbon atoms, and the photopolymerization initiator Omnirad819 (manufactured by IGM Resins BV) was changed from 0.5 parts by mass to 1.0 parts by mass of Omnirad184 (manufactured by IGM Resins BV).
[0089] [Comparative Example 1] A photocured double-sided PSA sheet with a release sheet was obtained using the same procedure as in Example 1, except that isobornyl acrylate (IBXA) was replaced with methyl acrylate (MA), a monofunctional (meth)acrylic acid ester monomer having an alkyl group with one carbon atom.
[0090] Comparative Example 2 A photocured double-sided PSA sheet with a release sheet was obtained using the same procedure as in Example 1, except that the solution (a-1) of base polymer (A-1) was changed to the solution (a-4) of base polymer (A-4) and 1,6-hexanediol diacrylate (A-HD-N) was changed to a trifunctional acrylic acid ester monomer, trimethylolpropane triacrylate (A-TMPT).
[0091] Comparative Example 3 A double-sided adhesive sheet with a release sheet was obtained using the same procedure as in Example 1, except that instead of adding a monofunctional (meth)acrylic acid ester monomer, a bifunctional (meth)acrylic acid ester monomer, and a photoinitiator, 0.5 parts by mass of an isocyanate-based crosslinking agent (D-110N, manufactured by Mitsui Chemicals, Inc.) was added.
[0092] (Evaluation and Measurement) <Oxygen permeability (P A )> [Making laminated sheets] The release sheet on the light release side of the photocured double-sided PSA sheets with release sheets (double-sided PSA sheet thickness: 100 μm) prepared in the Examples and Comparative Examples was peeled off, and a 20 μm unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Chemicals Co., Ltd.) was laminated using a hand roller to obtain a PSA sheet backed with unstretched polypropylene. Next, the release sheet on the heavy release side of the unstretched polypropylene-backed PSA sheet was peeled off, and the 100 μm-thick double-sided PSA sheet prepared in the Examples and Comparative Examples was laminated to the exposed adhesive surface so that the adhesive surfaces were in contact, obtaining a PSA sheet backed with unstretched polypropylene and having an adhesive layer thickness of 200 μm. Next, the release sheet on the heavy release side of the adhesive sheet, which was backed with unstretched propylene and had an adhesive layer 200 μm thick, was peeled off, and a 20 μm thick unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Chemicals Co., Ltd.) was laminated to the exposed adhesive surface to create a laminated sheet with a configuration of "unstretched polypropylene / adhesive layer (thickness 200 μm) / unstretched polypropylene."
[0093] [Oxygen permeability of laminated sheet (P L ) Measurement Oxygen permeability of laminated sheet (P L The oxygen permeability was measured using an oxygen permeability meter (OX-TRAN2 / 12 manufactured by MOCON) with a test cell area (measurement area) of 50 cm. 2 The oxygen permeability was measured after leaving the sample in an environment of 23°C, 50% relative humidity, and 1 atm for about 2 hours until the oxygen permeability stabilized. 2 The oxygen permeability of the laminated sheet (P L ) was calculated.
[0094] Oxygen permeability of unstretched polypropylene (P P ) Measurement Two 20 μm thick unstretched polypropylene films (CPP) were stacked to a thickness of 40 μm, and the oxygen permeability of the laminated sheet (P LThe oxygen permeability was measured using an oxygen permeability measuring device (OX-TRAN2 / 212 manufactured by MOCON) in the same manner as in "Measurement of oxygen permeability" above. 2 The oxygen permeability of unstretched polypropylene (P P ) was calculated.
[0095] [Oxygen permeability (P A ) calculation] The oxygen permeability (P L ) and the oxygen permeability of unstretched polypropylene (P P ) was calculated using the following formula (2) derived from the following formula (1) to calculate the oxygen permeability (P A ) was calculated. 1 / P L =1 / P A +1 / P P · · Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2)
[0096] <Suitable for copper mesh transparent conductive films> (Preparation of conductive film for evaluation) A transparent conductive film was prepared by forming a copper conductive layer on both sides of a 100 μm polyethylene terephthalate substrate using the method described in Example 3 of Japanese Patent No. 6607918. Subsequently, a grid-like wiring pattern with a pitch of 200 μm and a line width of 15 μm was formed on the conductive portions on both sides of this conductive film using photolithography, producing a copper mesh-based transparent conductive film for evaluation. A blackened film was then formed on the copper mesh using the method described in Example 3 of Japanese Patent No. 6607918.
[0097] (Preparation of evaluation samples) The release sheet on the light release side of the double-sided PSA sheets with release sheets prepared in the Examples and Comparative Examples was peeled off, and the sheet was attached to one side of a glass slide (S9112, manufactured by Matsunami Glass Co., Ltd.) using a hand roller. The release sheet on the heavy release side of the glass-backed PSA sheet was then peeled off, and the sheet was attached to the copper mesh-based transparent conductive film for evaluation prepared above. The double-sided PSA sheets prepared in the Examples and Comparative Examples were then attached to the surface of the copper mesh-based transparent conductive film of the laminate with a "glass / adhesive layer / copper mesh-based transparent conductive film" configuration. The release sheet on the heavy release side was then peeled off, and a glass slide (S9112, manufactured by Matsunami Glass Co., Ltd.) was attached using a vacuum laminating device (JE2020B-MVH, manufactured by Joyo Engineering Co., Ltd.) to produce a "glass / adhesive layer / copper mesh-based transparent conductive film / adhesive layer / glass" laminate. This laminate was then autoclaved for 30 minutes at 50°C and 0.5 MPa. Thereafter, the sample was left to stand for 24 hours under conditions of 23°C and a relative humidity of 50%, to prepare a sample for evaluating the suitability of the copper mesh-based transparent conductive film.
[0098] (Evaluation of suitability for copper mesh-based transparent conductive film) The copper mesh transparent conductive film suitability evaluation samples prepared above were treated in an oven at 95°C for 250 hours. After that, the appearance of the evaluation samples was visually observed, and the wiring portion was observed under an optical microscope. The copper mesh transparent conductive film suitability was evaluated based on the following evaluation criteria. Note that no lifting, peeling, or bubble formation occurred in any of the samples. A: The copper mesh is not visible to the naked eye. There is no change in color of the wiring even when observed under a microscope. B: The copper mesh is not visible to the naked eye, but under a microscope, a clear change in hue is visible in the wiring area, but the color change is uniform overall. C: The copper mesh is not visible to the naked eye, but a clear change in hue is observed in the wiring area under a microscope, and the hue differs between the edge and center of the sample. D: The edges of the sample appear slightly cloudy to the naked eye, and under a microscope there is a clear change in hue in the wiring area, and the edges and center of the sample also have different hues. E: The copper mesh is visible to the naked eye, and microscopic observation reveals a clear change in color in the wiring, giving the wiring a glossy appearance.
[0099] <Total light transmittance and haze value> The release sheet on the light release side of the double-sided pressure-sensitive adhesive sheet with release sheet (double-sided pressure-sensitive adhesive sheet thickness: 100 μm) prepared in the Examples and Comparative Examples was peeled off, and the sheet was attached to one side of a glass slide (S9112, manufactured by Matsunami Glass Co., Ltd.) using a hand roller. This laminate was then autoclaved for 30 minutes at 50°C and 0.5 MPa. The release sheet on the heavy release side was then peeled off to prepare an evaluation sample with a "glass / pressure-sensitive adhesive layer" configuration. The total light transmittance of the resulting sample was measured in accordance with JIS K 7361-1. The haze value of the resulting sample was also measured in accordance with JIS K 7136. These measurements were performed three times, and the average value was used for each measurement. An integrating sphere light transmittance measuring device (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used for the measurements. As a result, the double-sided pressure-sensitive adhesive sheets produced in the examples and comparative examples all had a total light transmittance of 90% to 100% in an environment of 23°C and 50% relative humidity, and a haze value of less than 1% in an environment of 23°C and 50% relative humidity.
[0100] <Gel fraction> Approximately 0.1 g of the adhesive layer was collected in a sample bottle, 30 ml of ethyl acetate was added, and the mixture was shaken for 24 hours. The contents of the sample bottle were then filtered through a 150-mesh stainless steel wire mesh, and the residue on the wire mesh was dried at 100°C for 1 hour to measure the dry weight W (g). The obtained dry weight was calculated using the following formula: Gel fraction (%) = (dry mass W / collected mass of adhesive sheet) × 100 The value calculated from the above was taken as the gel fraction of the pressure-sensitive adhesive sheet.
[0101] [Table 1]
[0102] When the double-sided pressure-sensitive adhesive sheet obtained in the examples was attached to a copper mesh-based transparent conductive film and treated under high-temperature conditions, the change in hue of the wiring portion was suppressed and the visibility of the copper mesh portion was suppressed. [Explanation of symbols]
[0103] 1 double-sided adhesive sheet with release sheet 11 Double-sided adhesive sheet (adhesive layer) 12a, 12b Release sheet
Claims
1. A (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms; a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked via a linking group derived from a linear diol having 4 to 12 carbon atoms; a photopolymerization initiator (C) other than a hydrogen abstraction type polymerization initiator; A double-sided pressure-sensitive adhesive sheet obtained by photocuring a pressure-sensitive adhesive composition containing an organotin compound (D), The (meth)acrylic copolymer (A) contains (a1) units derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, (a2) units derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, and (a3) units derived from a hydroxyl group-containing (meth)acrylate, the content of the monofunctional (meth)acrylic acid ester monomer (B1) is 0.1 to 10 parts by mass, and the content of the bifunctional (meth)acrylic acid ester monomer (B2) is 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (A); The oxygen permeability (P) of the double-sided PSA sheet was measured and calculated by the following measurement method. A ) is 2000ml / (m 2 - 1 day · 1 atm) or more; (Measurement method) The thickness of the double-sided pressure-sensitive adhesive sheet was set to 200 μm, and a 20 μm-thick non-oriented polypropylene film (CPP) was attached to each of both sides of the sheet to produce a laminated sheet having a layer structure of "CPP (20 μm) / double-sided sheet (pressure-sensitive adhesive layer 200 μm) / CPP (20 μm)". The amount of oxygen transmitted through the laminated sheet was measured using an oxygen transmission rate measuring device under an environment of 23° C., relative humidity 50%, and 1 atm. 2 The oxygen permeability (P L Similarly, the oxygen permeability (P P ) was calculated, and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P ・・・ Formula (1) P A =(P P ×P L ) / (P P -P L ) ………… Formula (2)
2. 2. The double-sided pressure-sensitive adhesive sheet according to claim 1, wherein the content of the organotin compound (D) is 0.001 to 0.5 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer (A).
3. 2. The double-sided pressure-sensitive adhesive sheet according to claim 1, having a total light transmittance of 80% or more.
4. The double-sided pressure-sensitive adhesive sheet according to claim 1 , having a gel fraction of 75 mass % or less.
5. A laminate comprising the double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 4 and a copper mesh-based transparent conductive film.
6. A display device comprising the double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 4 and a copper mesh-based transparent conductive film.
Citation Information
Patent Citations
Curable pressure-sensitive adhesive composition, pressure-sensitive adhesive, and pressure-sensitive adhesive sheet
JP2014133812A
Acrylic resin composition, acrylic adhesive, adhesive sheet, double-sided adhesive sheet, adhesive for transparent electrode, touch panel and image display device, and production method of adhesive layer-containing laminate
JP2014201709A
Manufacturing method of touch panel sensor
JP2015125563A
Ultraviolet-curable adhesive composition
JP2019052213A
Conductive laminated body for touch panel, and method for manufacturing conductive laminated body for touch panel
WO2016136117A1